Bidirectional histone monoaminylation dynamics regulate neural rhythmicity - Qingfei Zheng; Benjamin H. Weekley; David A. Vinson; Shuai Zhao; Ryan M. Bastle; Robert E. Thompson; Stephanie Stransky; Aarthi Ramakrishnan; Ashley M. Cunningham; Sohini Dutta; Jennifer C. Chan; Giuseppina Di Salvo; et al. (Nature, 2025)
Abstract Histone H3 monoaminylations at Gln5 represent an important family of epigenetic marks in brain that have critical roles in permissive gene expression1–3. We previously demonstrated that serotonylation4–10 and dopaminylation9,11–13 of Gln5 of histone H3 (H3Q5ser and H3Q5dop, respectively) are catalysed by transglutaminase 2 (TG2), and alter both local and global chromatin states. Here we found that TG2 additionally functions as an eraser and exchanger of H3 monoaminylations, including H3Q5 histaminylation (H3Q5his), which displays diurnally rhythmic expression in brain and contributes to circadian gene expression and behaviour. We found that H3Q5his, in contrast to H3Q5ser, inhibits the binding of WDR5, a core member of histone H3 Lys4 (H3K4) methyltransferase complexes, thereby antagonizing methyltransferase activities on H3K4. Taken together, these data elucidate a mechanism through which a single chromatin regulatory enzyme has the ability to sense chemical microenvironments to affect the epigenetic states of cells, the dynamics of which have critical roles in the regulation of neural rhythmicity.